A paradigm for achieving successful pediatric trauma verification in the absence of pediatric surgical specialists while ensuring quality of care. Issue 3 (March 2016) - Falcone, Richard A.; Milliken, William J.; Bensard, Denis D.; Haas, Lynn; Daugherty, Margot; Gray, Lisa; Tuggle, David W.; Garcia, Victor F.
Abstract : BACKGROUND: Pediatric trauma centers (PTCs) are concentrated in urban areas, leaving large areas where children do not have access. Although adult trauma centers (ATCs) often serve to fill the gap, disparities exist. Given the limited workforce in pediatric subspecialties, many adult centers that are called upon to care for children cannot sufficiently staff their program to meet the requirements of verification as a PTC. We hypothesized that ATCs in collaboration with a PTC could achieve successful American College of Surgeons (ACS) verification as a PTC with measurable improvements in care. This article serves to provide an initial description of this collaborative approach. METHODS: Beginning in 2008, a Level I PTC partnered with three ATC seeking ACS-PTC verification. The centers adopted a plan for education, simulation training, guidelines, and performance improvement support. Results of ACS verification, patient volumes, need to transfer patients, and impact on solid organ injury management were evaluated. RESULTS: Following partnership, each of the ATCs has achieved Level II PTC verification. As part of each review, the collaborative was noted to be a significant strength. Total pediatric patient volume increased from 128.1 to 162.1 a year ( p = 0.031), and transfers out decreased from 3.8% to 2.4% ( p = 0.032) from prepartnership to postpartnership periods. At the initial ATC partner site, 10.7 children per year with solid organ injury were treated before the partnership and 11.8 children per year after the partnership. Following partnership, we found significant reductions in length of stay, number of images, and laboratory draws among this limited population. CONCLUSION: The collaborative has resulted in ACS Level II PTC verification in the absence of on-site pediatric surgical specialists. In addition, more patients were safely cared for in their community without the need for transfer with improved quality of care. This paradigm may serve to advance the care of injured children at sites without access to pediatric surgical specialists through a collaborative partnership with an experienced Level I PTC. Further risk-adjusted analysis of outcomes will need to be performed in the future. LEVEL OF EVIDENCE: Therapeutic/care management, level IV. Abstract : Supplemental digital content is available in the text.